2014
DOI: 10.3892/or.2014.2994
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Akt by arsenic trioxide induces cell death via mitochondrial-mediated apoptotic signaling in SGC-7901 human gastric cancer cells

Abstract: Abstract. Arsenic trioxide (As 2 O 3 ) has been recognized as a potential chemotherapeutic agent, yet the details concerning its mechanism of action in solid cancers remain undetermined. The present study assessed the role of Akt in the cell death induced by As 2 O 3 . The MTT assay showed that As 2 O 3 suppressed the proliferation of SGC-7901 cells in a dose-and time-dependent manner. Characteristic apoptotic changes were observed in the As 2 O 3 -treated cells by Hoechst 33342 staining, and FACS analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Furthermore, the NF-κB inhibitor SN50 leads to an increase in the effect of LY294002 on inducing death of human gastric carcinoma cells through upregulated expression of p53, PUMA, and Beclin1 [ 43 ]. Several factors have been reported to induce apoptosis via the PI3K/Akt pathway in gastric carcinoma [ 44 , 45 , 46 , 47 , 48 ]. Apoptosis of gastric carcinoma cells induced by isoalantolactone was associated with the dissipation of mitochondrial membrane potential due to downregulation of Bcl-2 and upregulation of Bax [ 49 ].…”
Section: The Role Of the Pi3k/akt/mtor Pathway In The Biological Pmentioning
confidence: 99%
“…Furthermore, the NF-κB inhibitor SN50 leads to an increase in the effect of LY294002 on inducing death of human gastric carcinoma cells through upregulated expression of p53, PUMA, and Beclin1 [ 43 ]. Several factors have been reported to induce apoptosis via the PI3K/Akt pathway in gastric carcinoma [ 44 , 45 , 46 , 47 , 48 ]. Apoptosis of gastric carcinoma cells induced by isoalantolactone was associated with the dissipation of mitochondrial membrane potential due to downregulation of Bcl-2 and upregulation of Bax [ 49 ].…”
Section: The Role Of the Pi3k/akt/mtor Pathway In The Biological Pmentioning
confidence: 99%
“…A likely explanation for this phenomenon is the induction of ROS through arsenic toxicity, which in turn decreases AKT activity and promotes proapoptotic features. In human gastric cancer (SGC-7901) cell lines, ATO for up to 72 hours led to decreased phosphorylation at two AKT sites, Ser 473 and Thr308, although the protein levels stayed relatively same, indicating that arsenic can reduce activation of AKT rather than the total protein ( Gao et al, 2014 ). In another study led by Wang et al (2017) , arsenic disulfide has been found to inhibit the AKT/mTOR signaling pathway and induce autophagy and apoptosis in several osteosarcoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer cells, ATO was reported to inhibit cellular proliferation and induce cell cycle arrest via modulation of phosphatidylinositol 3-kinase/Akt (PI3K/Akt) and p53 signaling [ 1 ]. The pro-apoptotic effect of ATO in gastric cancer cells is also suggested by inhibition of Akt and mTOR signaling [ 2 ]. A recent study showed that ATO may inhibit the signal transducer and activator of transcription 3 (STAT3) activation in alpha-fetoprotein-producing gastric cancer cells, and thereby induce apoptosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%